The Influence of Parenting Styles on Children's Emotional Intelligence in Early Childhood Education: A Study at TK Sahabat Bekasi - Arwati, Sri; Supriyadi, Supriyadi; Priyani, Nina Yuminar (CV. Creative Tugu Pena, 2025)
This study aims to analyze the influence of parenting styles on the emotional intelligence of Group B children at TK Sahabat Bekasi. A quantitative approach with a survey method was employed, involving 32 children and their parents selected through total sampling. Research instruments comprised Likert-scale questionnaires measuring three parenting styles (democratic, authoritarian, and permissive) and children’s emotional intelligence. Data were analyzed using simple linear regression with SPSS 22. The findings revealed that parenting styles significantly affect children’s emotional intelligence (R² = 0.374; p < 0.05). The highest contribution came from the democratic parenting style (3.7%), followed by permissive (3.17%) and authoritarian (2.72%). These results confirm that democratic parenting—characterized by open communication, guided freedom, and respect for children’s opinions—is more effective in supporting emotional intelligence development. The study highlights the importance of consistently applying democratic parenting and suggests that educators provide parental education on positive parenting strategies.